2016
DOI: 10.1155/2016/3928714
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channels and Oxidative Stress as a Potential Link for the Diagnosis or Treatment of Liver Diseases

Abstract: Oxidative stress results from a disturbed balance between oxidation and antioxidant systems. Reactive oxygen species (ROS) and reactive nitrogen species (RNS) may be either harmful or beneficial to the cells. Ion channels are transmembrane proteins that participate in a large variety of cellular functions and have been implicated in the development of a variety of diseases. A significant amount of the available drugs in the market targets ion channels. These proteins have sulfhydryl groups of cysteine and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 210 publications
(198 reference statements)
2
44
0
2
Order By: Relevance
“…Previous reports suggested that TRPV4 is expressed in both hepatoma cell lines and primary hepatocytes (16)(17)(18)(19). Indeed, by performing RT-PCR on Huh7, HepG2, and PHH cells as well as PMHs, we could confirm an expression of TRPV4 in these cells (Supplemental Fig.…”
Section: Pharmacological Inhibition and Deletion Of Trpv4 Reduce Apapsupporting
confidence: 63%
See 1 more Smart Citation
“…Previous reports suggested that TRPV4 is expressed in both hepatoma cell lines and primary hepatocytes (16)(17)(18)(19). Indeed, by performing RT-PCR on Huh7, HepG2, and PHH cells as well as PMHs, we could confirm an expression of TRPV4 in these cells (Supplemental Fig.…”
Section: Pharmacological Inhibition and Deletion Of Trpv4 Reduce Apapsupporting
confidence: 63%
“…The ion channel TRP vanilloid 4 (TRPV4) is expressed in several tissues and is involved in diverse physiologic functions by sensing osmolarity, pressure, and heat but also reactive oxygen species (ROS) (14,15). Other than that TRPV4 was shown to be expressed in both hepatoma cell lines and native hepatocytes, little is known about the role of TRPV4 in the liver (16)(17)(18)(19). However, TRPV4 mediates ROS-induced cell damage associated with ischemia and reperfusion in both cardiomyocytes and in the CNS (20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Studies have shown that OS could be associated with neurodegenerative disorders, such as Alzheimer's and Parkinson's diseases, pathologies involving chronic inflammations with consequent higher levels of OS due to an increase of ROS and RNS production [23][24][25][26]. In this context, OS markers have received substantial attention in recent years and many of them have been studied, such as MDA and TEAC [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the target proteins are retained in their oxidized forms and are activated as long as the antioxidant activity is reduced. To date, several studies have shown that oxidative stress is involved in the modulation of activities of voltage-gated Ca 2+ (Gorlach et al, 2015;Ramirez et al, 2016), Na + , and K + (Sesti et al, 2010) channels and ligandgated receptors such as NMDA (Kamat et al, 2016), AMPA (Joshi et al, 2015), GABA (Bradley and Steinert, 2016), and RyR (Zima and Mazurek, 2016). However, there is limited evidence that directly identifies the oxidative modification of a channel protein based on molecular mechanisms.…”
Section: The Critical Role Of Ca 2+ In the Pathogenesis Of Neurodegenmentioning
confidence: 99%